2016
DOI: 10.1186/s12864-016-2940-7
|View full text |Cite
|
Sign up to set email alerts
|

Motif oriented high-resolution analysis of ChIP-seq data reveals the topological order of CTCF and cohesin proteins on DNA

Abstract: BackgroundChIP-seq provides a wealth of information on the approximate location of DNA-binding proteins genome-wide. It is known that the targeted motifs in most cases can be found at the peak centers. A high resolution mapping of ChIP-seq peaks could in principle allow the fine mapping of the protein constituents within protein complexes, but the current ChIP-seq analysis pipelines do not target the basepair resolution strand specific mapping of peak summits.ResultsThe approach proposed here is based on i) lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…We calculated the distance between G-quadruplexes/CTCF/RAD21/ SMC3 ChIP-seq peaks and forward/reverse CTCF motifs ( Figure S3A-B). In line with previous study, we found a characteristic shift pattern between CTCF motifs and cohesin protein ChIP-seq peaks [46]. Surprisingly, similar to cohesin protein ChIP-seq peaks, G-quadruplexes tend to distribute downstream of forward CTCF motifs (average distance = 3.15 bp, 2.18 bp, and 5.21 bp for G-quadruplexes, SMC3, and RAD21, respectively) and upstream of reverse CTCF motifs (average distance = −4.49 bp, −2.31 bp, and −5.79 bp for G-quadruplexes, SMC3, and RAD21, respectively).…”
Section: G-quadruplexes Are Correlated With the Role Of Ctcf In Chromsupporting
confidence: 93%
“…We calculated the distance between G-quadruplexes/CTCF/RAD21/ SMC3 ChIP-seq peaks and forward/reverse CTCF motifs ( Figure S3A-B). In line with previous study, we found a characteristic shift pattern between CTCF motifs and cohesin protein ChIP-seq peaks [46]. Surprisingly, similar to cohesin protein ChIP-seq peaks, G-quadruplexes tend to distribute downstream of forward CTCF motifs (average distance = 3.15 bp, 2.18 bp, and 5.21 bp for G-quadruplexes, SMC3, and RAD21, respectively) and upstream of reverse CTCF motifs (average distance = −4.49 bp, −2.31 bp, and −5.79 bp for G-quadruplexes, SMC3, and RAD21, respectively).…”
Section: G-quadruplexes Are Correlated With the Role Of Ctcf In Chromsupporting
confidence: 93%
“…In contrast, the C terminus of CTCF was dispensable for cohesin occupancy and loop formation, challenging previous work reporting that the C terminus of CTCF directly interacts with SA2, an external subunit of cohesin ring, and thus provides a bridge between CTCF and the cohesin complex (34). A role for the N terminus of CTCF in cohesin retention is consistent with high-resolution ChIP-seq analysis showing that cohesin binding tends to be shifted toward the N terminus of CTCF (37). Besides, an alternative form of CTCF missing its N terminus was shown to be unable to retain cohesin at CTCF binding sites (55).…”
Section: Discussionsupporting
confidence: 72%
“…However, precise deletion of the same peptide sequence from the C terminus of CTCF does not disrupt the interaction of CTCF with cohesin, as shown in two independent studies (35,36). Furthermore, a highresolution analysis of ChIP-seq data based on the orientation of -V5-TAG CTCF consensus sequences showed that cohesin occupancy at CTCF binding sites is usually shifted toward the N terminus rather than the C terminus of CTCF (26,37). To map the CTCF domain responsible for cohesin binding in vivo, we employed the mut CH12 cell system described above (Fig.…”
Section: Ctcf and Nibpl Are Sufficient To Explain The Genomic Distribmentioning
confidence: 87%
“…CTCF-depletion studies identified the function of CTCF in association with chromatin structure in mouse embryonic stem cells ( 2 ). For maintaining stable genomic complex, CTCF and the cohesin complex, consisting of SMC3, SMC1, RAD21, and STAG1 or STAG2, can co-localize ( 13 ). Moreover, global analysis of CTCF, SMC3, and RAD1 shift-banding patterns have demonstrated the proximity of protein-DNA binding motif sequences ( 13 ).…”
Section: Diverse Roles Of Ctcfmentioning
confidence: 99%